The Impact of Stores Management on the Operation of the Production Industries in Uganda: A Case Study of Coca-Cola Company Namanve Plant - James Alphonse Raimondo (Uganda Christian University, 2023)
This study examined the impact of stores management on the operation of production industries in Uganda. The objectives of the study were; to examine the influence of storage management practices on the operation of Coca-Cola Company, to establish the effect of materials handling practices on the operation of Coca-Cola Company and to examine the effect of lead time management practices on the operation of Coca-Cola Company, Namanve. A cross-sectional study design using a sample of 52 respondents was adopted. Simple random sampling and purposive sampling techniques were used to select the respondents and data was collected using well designed structured questionnaires. Findings reveal that the functions of stores department have been carefully planned in the company as shown by a mean value of 4.16. It was also found that there are timely deliveries in their company due to proper materials handling practices as reflected by a mean value of 3.78. The study also found out that information lead time in the company has been reduced by using modern communication system as shown by a mean value of 4.18. In conclusion, there is a significant positive relationship between stores management and operation of production industries. The study recommends that Coca-Cola Company should adopt proactive attitudes towards the issue of proper store management practices. The study recommends that Just-in-time systems should also be integrated by the firms. In addition, the study recommends that there is need for the top management at Coca-Cola Company to adopt the use of information technology, that will not only help in information sharing, but also will help in speeding orders from suppliers hence shortening the lead time.
This is a dissertation.